Dynamic Regulation of TCR–Microclusters and the Microsynapse for T Cell Activation - Hashimoto-Tane, Akiko; Saito, Takashi (Frontiers in Immunology, 2016)
The interaction between a T cell and an antigen-presenting cell (APC) is the initiating event in T cell-mediated adaptive immunity. The Immunological Synapse (IS) is formed at the interface between these two cell types, and is the site where antigen (Ag)-specific recognition and activation are induced through the T cell receptor (TCR). This occurs at the center of the IS and cell adhesion is supported through integrins in the area surrounding the TCR. Recently, this model has been revised based on data indicating that the initial Ag-specific activation signal is triggered prior to IS formation at TCR-microclusters (MCs), sites where TCR, kinases and adaptors of TCR proximal downstream signaling molecules accumulate as an activation signaling cluster. TCR-MCs then move into the center of the cell-cell interface to generate the cSMAC. This translocation of TCR-MCs is mediated initially by the actin cytoskeleton and then by dynein-induced movement along microtubules. The translocation of TCR-MCs and cSMAC formation is induced upon strong TCR stimulation through the assembly of a TCR-dynein super complex with microtubules. The Ag-specific activation signal is induced at TCR-MCs, but the adhesion signal is now shown to be induced by generating a “microsynapse”, which is composed of a core of TCR-MCs and the surrounding adhesion ring of integrin and focal adhesion molecules. Since the microsynapse is critical for activation, particularly under weak TCR stimulation, this structure supports a weak TCR signal through a cell-cell adhesion signal. The microsynapse has a structure similar to the IS but on a micro-scale, and regulates Ag-specific activation as well as cell-cell adhesion. We describe here the dynamic regulation of TCR-MCs, responsible for inducing Ag-specific activation signals, and the microsynapse, responsible for adhesion signals critical for cell-cell interactions, and their interrelationship.